2010
DOI: 10.1002/ca.21045
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation of the nasal septum: Correlation among septal components

Abstract: The nasal septum consists of multiple components with various developmental origins and is considered a mosaic structure. Few studies have focused on anatomical relationships among the components of the nasal septum, even though they are essential for clinical assessments of morphological abnormalities in the nasal septum. This study was performed to evaluate anatomical correlations among components of the nasal septum using computed tomography (CT) of the paranasal sinus. We studied images from CT scans of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 8 publications
(10 reference statements)
4
25
1
2
Order By: Relevance
“…The mean area of the septal cartilage (872.47 mm 2 ) was significantly larger than those found in the cadaver study (817.2 mm 2 ) [5], in the PNS CT study (752.76 mm 2 ) [8], and in the MRI study (692 mm 2 ) [9]. The authors assume that the reason for the larger area values of the septal cartilage in our study is the inclusion of the SP, which is the septal tail, with a mean area of 69.46 mm 2 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The mean area of the septal cartilage (872.47 mm 2 ) was significantly larger than those found in the cadaver study (817.2 mm 2 ) [5], in the PNS CT study (752.76 mm 2 ) [8], and in the MRI study (692 mm 2 ) [9]. The authors assume that the reason for the larger area values of the septal cartilage in our study is the inclusion of the SP, which is the septal tail, with a mean area of 69.46 mm 2 .…”
Section: Discussionmentioning
confidence: 94%
“…In a gender comparison, most studies [8,9] have reported that the total nasal septum area was significantly larger in the males than females, but the septal cartilage was not significantly different in size. However, in this study, the areas of both the total nasal septum and the septal cartilage were significantly greater in the males than females (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…1,3,6,[14][15][16] The intricate anatomy of the nose and its relationship to nasal support, respiratory function, and facial development have been well established. [1][2][3][4]17 The placement of autogenous septal cartilage in rhinoplasty and complex nasal reconstruction has also been extensively discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli, such as mechanical forces or growth factors, may be applied to improve neocartilage functional properties and organization [100]. It should be noted that both nasal and articular cartilages are hyaline and result from endochondral ossification [101].…”
Section: 3: Nasal Cartilage Tissue-engineeringmentioning
confidence: 99%